A New International Division of Labor in Europe: Offshoring and Outsourcing to Eastern Europe - Dalia Marin (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
Europe is reorganizing its international value chain. I document these changes in Europe's international organization of production with new survey data of Austrian and German firms investing in Eastern Europe. I show estimates of the share of intra-firm trade between Austria and Germany on the one hand and Eastern Europe on the other. Furthermore, I present empirical evidence of the drivers of the new division of labor in Europe. I find among other things that falling trade costs and falling corruption levels as well as improvements in the contracting environment in Eastern Europe are affecting the level of intra-firm imports from Eastern Europe. They are also favoring outsourcing over offshoring. Low organizational costs of hierarchies and large costs of hold-up (when there are no alternative investors in Old Europe or no alternative suppliers in Eastern Europe) are favoring offshoring over outsourcing. Tax holidays granted by host countries in Eastern Europe also mildly affect the organizational choice.
urn:nbn:de:bvb:19-epub-714-8
Keywords: D23; D51; F11; L14; O11; 330; the empirics of global sourcing; intra-firm trade; contract enforcement; comparative advantage in Eastern Europe; empirical test of the theory of the firm